Developments in computational optimization techniques of conjugate gradient coefficient, search direction, Broyden-Fletcher-Goldfarb-Shanno, symmetric-rank one and Davidon-Fletcher-Powell quasi-Newton methods. - Adams*†, A.; Abubakar*‡, U.Y.; Abubakar*, U.; Yakubu*, Y. (International Journal of Mathematical Analysis and Modelling, 2023)
In this paper, we propose a modified Conjugate Gradient Coefficient (